A colorful walk on the mental number line: Striving for the right direction - Cohen Kadosh, R; Tzelgov, J; Henik, A (2008)
Verguts and Van Opstal [Verguts, T., and Van Opstal, F. (2008). A colorful walk, but is it on the mental number line? Reply to Cohen Kadosh, Tzelgov, and Henik, Cognition, 106, 558-563] cleverly explained the results of Cohen Kadosh, Tzelgov, and Henik [Cohen Kadosh, R., Tzelgov, J., and Henik, A. (2008). A synesthetic walk on the mental number line: The size effect, Cognition, 106, 548-557] as a result of different association strength between the size of a number and its color in synesthesia. Here we present three challenges to their alternative explanation, and support our original suggestion. © 2007 Elsevier B.V. All rights reserved.